Analysis Of The Level Of Spike Skills In The Volleyball Club Of The Tunas Hope And Bry Boys In Taba Tengah Village - Pratama, Deki; Supriyanto, Supriyanto; Martiani, Martha Heriniazwi (Journal of Education, 2025)
This study aims to determine the level of spike skills at the Tunas Harapan and Bry men's volleyball clubs in Taba Tengah village. This research method is a research study used in this study in the category of Quantitative Descriptive research. The samples in this study were athletes of the tunas hope club and the bry club. The test results of hope tunas club athletes who have a good category of 4 people (27%), 9 people (60%) enough category, 2 people (13%) less category, bry club who have a good category of 4 people (26.7%), 8 people (53.3%) enough category, 3 people (20%) less category. So it can be concluded that the analysis of spike techniques in volleyball athletes Tunas Harapan club and Bry club in Taba tengah Village based on average is in the sufficient category.